The renaissance of a local wine industry: The relevance of social capital for business innovation in DOQ El Priorat, Catalonia - MarÃa José Fernández Aldecua; Yancy Vaillant; Esteban Lafuente; Jorge Moreno Gómez (Wine Economics and Policy)
The paper presents the results of a case study that aims to investigate whether the presence of both bridging and bonding social capital, acting together, can stimulate entrepreneurial innovation within the wine industry at a regional level. The study also investigates the manner in which both types of social capital interact to motivate such innovation. This is done through the analysis of the Catalan region of Priorat, and more specifically the entrepreneurial innovations that the regionâs wine sector experienced over a twenty year period at the turn of the current millennium. The results indicate that both forms of social capital do not act in isolation, but on the contrary are jointly responsible for stimulating innovation within the wine-producing network. Keywords: Social capital, Social networks, Regional innovation, Entrepreneurs, Catalonia